Dynamic Expression and the Role of BDNF in Exercise-induced Skeletal Muscle Regeneration - Yu, Tao; Chang, Yun; Gao, Xiao Lin; Li, Han; Zhao, Peng (International Journal of Sports Medicine, 2017)
Brain-derived neurotrophic factor (BDNF) is a myokine. However, its role in skeletal muscle has not been well elucidated. In this study, we aimed to investigate its expression profile in skeletal muscle following downhill running and to explore its functions. Male Sprague Dawley rats were assigned to sedentary and downhill running groups. Tail vein blood, total mRNA and protein from soleus muscle was obtained from rats at different time points post-exercise (1d, 3d, 5d, 7d and 14d). We found a significant elevation of BDNF mRNA level 5d and 7d post-exercise (p<0.05), increased BDNF protein level 1d, 3d, 7d and 14d post-exercise (p<0.05), and continuously elevated serum BDNF level (p<0.05). In addition, serum creatine kinase activity was increased 5d following exercise (p<0.05); expression of MyoD was elevated (p<0.05); disruption of myofibers and centralized nuclei in damaged myofibers were clearly observed 1d and 5d post-exercise, respectively. Moreover, AMPK phosphorylation was present 1d post-exercise (p<0.05), while AKT was phosphorylated for 5d post-exercise (p<0.05). In conclusion, downhill running induces a time-dependent up-regulation of BDNF in skeletal muscle, which is involved in exercise-induced skeletal muscle regeneration.
Keywords: brain-derived neurotrophic factor; downhill running; skeletal muscle regeneration; time-dependent